Southeast Asian port development : policy and initiatives towards achieving 2030 agenda on sustainable development goals - Hanizah Idris, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ports are catalyst for economic growth and development of countries including in Southeast Asia where more than 90% of cargos are exported by sea. Port of Singapore, Port Klang and Port of Tanjung Pelepas are classified as mega ports in the region while other ports such as Laem Chabang, Manila, Tanjung Priok and Ho Chi Minh ports are classified as national gateway ports. Following the declaration of a new 2030 Agenda on Sustainable Development in 2015, the Heads of States and Government and High Representatives are committed to achieving sustainable development in its three dimensions; economic, social and environment in a balanced and integrated manner. For Southeast Asian countries, the target under SDG17 that is to strengthen the means of implementation and revitalize the global for sustainable development is crucial where SDGs can be met within the framework of revitalized global partnership for sustainable development. The aim of this study is to discuss the policy and other initiatives taken by the maritime sector in selective countries in Southeast Asia in order to achieve the 2030 Agenda on Sustainable Development including its SDG17. Finding indicates that it is crucial for ports globally include in the Southeast Asian region to adopt sustainable development concept in its policy and port management in line with the 2030 agenda on the sustainable development, not only to minimize the impact of ports on environment but also community, safety and security as well as strengthening the port governance in the era of the “new normal”.